Hubungan Self Efficacy dengan Kinerja Perawat Pelaksana di Ruang Rawat Inap Irina C RSUP Prof. Dr. R. D. Kandou Manado - Langi, Marcella Margaretha; Dina Mariana Larira; Lenny Gannika (Mapalus Nursing Science Journal, 2025)
Background: Nurses' performance has a major impact on the quality of health services in hospitals. One of the main factors affecting this performance is self-efficacy, which is the nurse's confidence in carrying out nursing tasks. High self-efficacy makes nurses more confident and able to face various challenges, and provide maximum care to patients. Purpose: The purpose of this study was to determine the relationship between self-efficacy and performance of executive nurses. Methods: This research uses quantitative research methods with a cross-sectional approach with a sample size of 84 nurses taken using total sampling technique. The instruments used were self-efficacy questionnaire and nurse performance questionnaire. Data analysis was performed using Fisher's Exact Test alternative test to see the relationship between the two variables. Results: The results of data analysis showed a p value = 0.000 (p <0.05) which means there is a significant relationship between self-efficacy and nurse performance. Conclusion: Self efficacy has a significant relationship with nurse performance. Increased self-efficacy among nurses can contribute to improved performance, which in turn has a positive impact on the quality of health services in hospitals.